ANALISIS PENGARUH KURS DAN INFLASI TERHADAP INVESTASI DI SUMATERA UTARA PERIODE 2001-2020 - Ade Andriani Batubara (Niagawan, 2022)
Investment is one of the factors driving the economy in a region. The purpose of this study was to analyze the effect of exchange rate and inflation on investment in North Sumatra Province. The analytical model used is multiple linear regression analysis using secondary data for 2001-2020 sourced from the Provincial BPS. The results show that a) the exchange rate has a positive and significant effect on investment in North Sumatra Province, b) inflation has a negative and significant effect on investment in North Sumatra Province, c) simultaneously the exchange rate and inflation have a significant effect on investment in North Sumatra Province with the second contribution. variable by 0.85 percent. And the most dominant variable influencing investment in North Sumatra Province is the exchange rate variable.Keywords: Investment, Exchange Rate, Inflation